Use of Pillared Clay-Based Catalysts for Wastewater Treatment through Fenton-Like Processes - J. Herney-Ramírez (2010)
Clays, both natural and physical-chemically modified, are attractive materials for the preparation of supported catalysts. In this chapter, a review is made regarding the use of pillared interlayered clays (PILCs) in heterogeneous Fenton-like advanced oxidation processes. Their applications in pollutants degradation is summarized, with particular emphasis on the effect of the main operating conditions (e.g., initial H2O2 or parent compound concentration, catalyst load, pH, or temperature) on oxidation efficiency. Special attention is also given to the type of catalyst or precursor used, to the importance and advantages of the heterogeneous versus homogeneous process, and to significant aspects like catalyst stability. Among the technological issues that are of concern, the importance of using continuous flow reactors (e.g., fixed-bed) is discussed. Finally, some mechanistic studies are reviewed as well as modeling works, based on phenomenological or semi-empiric models (e.g., using statistic tools like design of experiments).